The Language of Resilience: Ecolinguistics Insights into Psychological Coping with Environmental Crisis - Hariati, Puji (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study explores the role of language in fostering psychological resilience amid the global environmental crisis. The problem addressed lies in the lack of interdisciplinary research connecting ecolinguistics and ecopsychology to understand how linguistic expressions, metaphors, narratives, and discursive frames, function as coping mechanisms for eco-anxiety and ecological grief. Using a qualitative method with Critical Discourse Analysis (CDA), the study analyzed textual and interview data from eco-activists, educators, and individuals experiencing environmental distress. Four major themes emerged: narratives of connection, metaphors of regeneration, emotional reframing, and linguistic activism. Findings reveal that language serves not only as a communicative medium but also as a therapeutic and symbolic tool that transforms despair into agency and grief into growth. The study concludes that cultivating a “language of resilience” is essential to strengthen both psychological well-being and ecological consciousness in facing planetary trauma. Keywords: Ecolinguistic, Psychological, Environmental